2015
DOI: 10.1016/j.nrl.2013.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Aptitudes de aprendizaje y desempeño escolar en niños y jóvenes con epilepsia ausencia

Abstract: Children treated pharmacologically for absence epilepsy, whose seizures are controlled, have normal academic abilities and skills for their age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In total, data were available for 29 samples. In total, 17 cohorts reported only on CAE (Berg et al, 2011; Berg et al, 2014; Caplan et al, 2008; Cerminara et al, 2013; Cheng et al, 2017; Conant et al, 2010; D’Agati et al, 2012; Gencpinar et al, 2016; Guerrini et al, 2015; Kernan et al, 2012; Levav et al, 2002; Lopes et al, 2014; Lopes et al, 2013; Masur et al, 2013; Mostafa et al, 2014; Nolan et al, 2004; Oostrom et al, 2003; Schraegle et al, 2016; Shinnar et al, 2017; Siren et al, 2007; Talero-Gutierrez et al, 2015; Vega et al, 2010; Wirrell et al, 1996) and in 12 cohorts reports were available in children with AE or a combination of CAE with JAE (Conde-Guzon & Cancho-Candela, 2012; Covanis et al, 1992; Fastenau et al, 2009; Franzoni et al, 2015; Henkin et al, 2003; Henkin et al, 2005; Oostrom et al, 2003; Pavone et al, 2001; Sinclair & Unwala, 2007; Siren et al, 2007; Talero-Gutierrez et al, 2015; Urena-Hornos et al, 2004; Vanasse et al, 2005; Verrotti et al, 2011). No studies were available reporting on JAE exclusively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, data were available for 29 samples. In total, 17 cohorts reported only on CAE (Berg et al, 2011; Berg et al, 2014; Caplan et al, 2008; Cerminara et al, 2013; Cheng et al, 2017; Conant et al, 2010; D’Agati et al, 2012; Gencpinar et al, 2016; Guerrini et al, 2015; Kernan et al, 2012; Levav et al, 2002; Lopes et al, 2014; Lopes et al, 2013; Masur et al, 2013; Mostafa et al, 2014; Nolan et al, 2004; Oostrom et al, 2003; Schraegle et al, 2016; Shinnar et al, 2017; Siren et al, 2007; Talero-Gutierrez et al, 2015; Vega et al, 2010; Wirrell et al, 1996) and in 12 cohorts reports were available in children with AE or a combination of CAE with JAE (Conde-Guzon & Cancho-Candela, 2012; Covanis et al, 1992; Fastenau et al, 2009; Franzoni et al, 2015; Henkin et al, 2003; Henkin et al, 2005; Oostrom et al, 2003; Pavone et al, 2001; Sinclair & Unwala, 2007; Siren et al, 2007; Talero-Gutierrez et al, 2015; Urena-Hornos et al, 2004; Vanasse et al, 2005; Verrotti et al, 2011). No studies were available reporting on JAE exclusively.…”
Section: Resultsmentioning
confidence: 99%
“…The number of studies reporting on cognitive performance in AE has been growing steadily and warrants a formal review (Berg, Caplan, & Hesdorffer, 2011; Berg, Levy, Testa, & Blumenfeld, 2014; Caplan et al, 2008; Cerminara et al, 2013; Cheng et al, 2017; Conant, Wilfong, Inglese, & Schwarte, 2010; Conde-Guzon & Cancho-Candela, 2012; Covanis, Skiadas, Loli, Lada, & Theodorou, 1992; D’Agati, Cerminara, Casarelli, Pitzianti, & Curatolo, 2012; Fastenau et al, 2009; Franzoni et al, 2015; Gencpinar et al, 2016; Guerrini et al, 2015; Henkin et al, 2003; Henkin et al, 2005; Kernan et al, 2012; Levav et al, 2002; Lopes, Monteiro, Fonseca, Robalo, & Simoes, 2014; Lopes et al, 2013; Masur et al, 2013; Mostafa, Talaat, Shalaby, El-Fayoumy, & Labib, 2014; Nolan et al, 2004; Oostrom et al, 2003; Pavone et al, 2001; Schraegle, Nussbaum, & Stefanatos, 2016; Shinnar et al, 2017; Sinclair & Unwala, 2007; Siren et al, 2007; Talero-Gutierrez, Sanchez-Torres, & Velez-van-Meerbeke, 2015; Urena-Hornos et al, 2004; Vanasse, Beland, Carmant, & Lassonde, 2005; Vega et al, 2010; Verrotti et al, 2011; Wirrell, Camfield, Camfield, Gordon, & Dooley, 1996). A previous meta-analysis in idiopathic generalized epilepsy found significant impairments in general cognitive ability and across a wide variety of other cognitive domains (Loughman, Bowden, & D'Souza, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Different types of learning problems in children with epilepsy are described in the literature, not only as a consequence of failure in the cognitive sphere but also secondary to lack of attention, memory or language disorders, to name a few 29 . Battistini et al 30 found a greater incidence of disorders specific to learning in 87% of the cases of patients with epilepsy.…”
Section: Discussionmentioning
confidence: 99%